Problems of selecting an anticoagulant for secondary stroke prevention in patients with atrial fibrillation - V. V. Gusev; O. A. Lvova; N. A. Shamalov (Кардиоваскулярная терапия и профилактика)
The article describes the urgent problem of ischemic stroke prevention in patients with atrial fibrillation. It is proved that ischemic stroke in combination with AF is the most severe in terms of developing stable motor and speech disorders and disability. The frail older patients, as well as patients with swallowing disorders and reduced medical adherence present a special problem from this point of view. The most famous clinical studies on secondary prevention of cardioembolic stroke are RE-LY, ROCKET-AF, and ARISTOTLE. Based on subanalyses of randomized controlled trials, direct oral anticoagulants demonstrated a favorable efficacy profile in patients with atrial fibrillation and stroke/ transient ischemic attack, but the level of knowledge on each of them remained different. A number of advantages of rivaroxaban for primary and secondary prevention of stroke in patients with atrial fibrillation, including the elderly and patients with cognitive impairments and swallowing disorders, have been demonstrated.